Energy harvesting estimation from the vibration of a simply supported beam - Rajora A.; Dwivedi A.; Vyas A.; Gupta S.; Tyagi A. (My University, 2025)
Vibration-based energy harvesting has been investigated in this paper with the goal to utilize the ambient vibration energy to power small electronic components by converting vibration energy into electrical energy. A simply supported beam with a bonded high density piezoelectric patch to the surface is considered for the analysis. Analytical model for free vibration analysis is developed by starting with the linear constitutive relations for the beam and the patch. The equation of motion for transverse vibration of the beam is developed by considering the elastic as well as electrical properties in the generalized Hookes law and accordingly a transverse displacement function satisfying the simply supported boundary conditions is used for achieving the modal frequencies. Additionally, an analytical model is developed in order to estimate the energy generated under the action of a harmonic force applied on the surface of the patch. The results of the analytical model are validated using simulation software ANSYS and COMSOL. The developed analytical model is used to study the behavior of a simply supported harvester with various patch dimensions and locations. This paper throws light on parametric studies of eigen frequencies as well as extracted power corresponding to operating conditions.